Method for deeply purifying nickel-cobalt solution

Through the electroflocculation method combined with the deep purification method of fine filtration, the problem of broken particles passing through filtration during the adsorption and removal of oil by activated carbon is solved, and efficient purification of nickel-cobalt solution is achieved, and the purity and appearance quality of the product are improved.

CN119491110APending Publication Date: 2025-02-21广西银亿新材料有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411527738.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, partially damaged particles are easily penetrated and filtered when activated carbon adsorbsorbs and removes oil, resulting in poor product appearance quality and low product purity.

Method used

The broken carbon particles in the nickel-cobalt solution were removed by electroflocculation. By using molybdenum metal as anode in the electrolytic cell, molybdate colloid was generated, the carbon particles were adsorbed and settled, and the solution was deeply purified in combination with the refined filtration step.

Benefits of technology

It effectively removes damaged carbon particles in nickel-cobalt solution, improves the appearance quality and purity of the product, and is suitable for the production of high-purity nickel salts, cobalt salt crystals, and high-purity metal nickel and cobalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491110A_ABST
    Figure CN119491110A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrometallurgy, and particularly relates to a nickel-cobalt solution deep purification method which comprises the following steps: (1) oil removal: removing oil from a nickel-cobalt solution with activated carbon to obtain an oil-removed solution; the nickel-cobalt solution is selected from one of cobalt nickel sulfate, cobalt nickel chloride and cobalt nickel nitrate, and the nickel-cobalt solution contains oil; (2) adjusting the pH value: adding inorganic acid or liquid caustic soda into the oil-removed solution, and adjusting the pH value of the solution to 3.0-4.0 to obtain a carbon-removed solution; and (3) carbon removal: transferring the pre-carbon-removal solution into an electrolytic bath, respectively inserting a cathode plate and an anode plate into the pre-carbon-removal solution, electrifying, carrying out electric flocculation carbon removal, and carrying out refined filtration after carbon removal to obtain the purified nickel-cobalt solution. According to the method, only a small number of anodes are consumed, new impurities are not introduced, the cleanliness of the solution is high, and the finally obtained nickel-cobalt solution is suitable for producing high-purity nickel salt, cobalt salt crystals, metal nickel and metal cobalt and has important significance on extraction and application of high-purity nickel and cobalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrometallurgy, and in particular relates to a method for deep purification of a nickel-cobalt solution. Background Art

[0002] Nickel and cobalt are important raw materials for positive electrode materials of lithium-ion batteries in the field of new energy vehicles. They are usually used in the form of metal nickel, metal cobalt, nickel salts, cobalt salts, etc. to produce positive electrode materials, and are ultimately used in lithium-ion batteries. Cobalt can also be widely used in the field of electronic chemicals and the preparation of special alloys. It is an important material for the preparation of components such as magnetic recording, magnetic recording heads, optoelectronic devices, magnetic sensors, and integrated circuits. Cobalt with a purity of 99.9% to 99.99% has been widely used in the manufacture of magnetic materials and superalloys, and cobalt with a purity of 99.999% or even higher is used as a target material for advanced electronic components. In recent years, with the increase in demand for high-nickel and ultra-high-nickel positive electrode materials and higher requirements for battery safety performance, correspondingly, new requirements have been continuously put forward for the purity of its downstream products. The deep purification method of nickel-cobalt solution has become the key to improving the purity of the product. In order to adapt to the new market, it is necessary to develop a method for deep purification of nickel-cobalt solution. The purified nickel-cobalt solution can be used to produce high-purity nickel metal, high-purity cobalt metal, or high-purity nickel salt and cobalt salt crystals.

[0003] There are not many cobalt ore resources in the world, and there are few independent cobalt deposits. Cobalt mainly exists as an associated element. For example, in the nickel hydroxide intermediate produced from laterite nickel ore, there is some cobalt associated with it, which exists in the form of hydroxide and some oxides. In the process of extracting nickel and cobalt, nickel and cobalt are generally dissolved out at the same time by leaching agents, and iron, aluminum, silicon and other substances that are easy to form colloids under acidic conditions are removed by chemical methods in advance, calcium and magnesium ions are removed, and impurities are extracted by solvent extraction, and nickel and cobalt ions are extracted and separated, and finally a refined nickel salt solution (raffinate) and an organic phase loaded with cobalt are obtained. Commonly used extractants are acidic phosphine extractants P507 and Cyanex272. After degreasing, the refined nickel salt solution can be used to produce nickel salt crystals or electrolytic production of metallic nickel. The organic phase loaded with cobalt is washed and stripped to obtain a refined cobalt salt solution (stripping solution). After degreasing, the stripping solution obtained from the refined cobalt salt solution can be used to produce cobalt salt crystals or electrolytic production of metallic cobalt. The commonly used methods for purifying and removing impurities / oil from refined nickel salt solutions or refined cobalt salt solutions in the prior art mainly include: (1) primary filtration, fine filtration or enhanced filtration. This method can remove insoluble particles, impurities, insoluble microparticles, increase the cleanliness of the solution and thus improve the purity of the final product. However, in practice, fine filtration can generally only intercept microparticles with a diameter greater than 1 μm, while smaller microparticles cannot be intercepted. After the system has been in operation for a long time, when it is used to produce high-purity nickel salt and cobalt salt crystals, some microparticles smaller than 1 μm will be wrapped by the crystals, and the crystals will produce color, affecting product quality; (2) adsorption and oil removal by easily available inorganic materials such as activated carbon, fly ash, and bentonite. This method is more commonly used. Although the mechanical properties of the adsorbent are good, it is still inevitable that the adsorbent will be damaged. In particular, after damage, some microparticles are very small. The microparticles that pass through the filter after fine filtration cannot be observed by the naked eye, but will eventually be wrapped by the crystals when producing high-purity nickel salt and cobalt salt crystals, producing color that affects product quality; when the adsorbent is used to produce high-purity nickel salt and cobalt salt crystals, the adsorbent will be damaged. When producing metallic nickel and metallic cobalt, particles smaller than 1 μm are adsorbed on the cathode surface under the action of the electric field, resulting in nickel or cobalt being deposited on the cathode surface to form protrusions. The cathode surface flatness is poor and cannot be eliminated by post-treatment measures, affecting the appearance quality. In particular, after the electrolysis system has been running for a long time, since part of the anode liquid is returned for electrolysis, the damaged tiny adsorbent has a more significant impact on the product appearance quality. (3) Ion exchange resin adsorption degreasing or extraction chromatography to purify the solution. The adsorption and regeneration cycle of ion exchange resin is long, which is not conducive to cost saving. If the solution contains solid particles or the viscosity is too high, it will cause clogging of porous materials. If there are surfactants in the solution, it will destroy the surface properties of the resin and cause material failure. Therefore, it has not been widely used. (4) Membrane separation method. Because the membrane is easily contaminated and the pore size is blocked, especially when the concentration of particles or impurities in the solution is high, the membrane is contaminated faster. The regeneration procedure is complicated, which is not conducive to improving production efficiency and has a narrow application range.

[0004] Although there is no clear requirement for the carbon content in high-purity nickel salt and cobalt salt products, the damaged carbon particles are easily wrapped by nickel salt and cobalt salt crystals, resulting in poor product appearance quality. The standard documents for high-purity nickel and cobalt metals clearly stipulate the carbon content. Correspondingly, the higher the metal purity, the higher the carbon content requirement. The carbon content of cobalt with grade 9830 is required to be less than 0.1%, the carbon content of cobalt with grade 9998 is required to be less than 0.004%, the carbon content of nickel with grade 9920 is required to be less than 0.1%, and the carbon content of nickel with grade 9999 is also required to be less than 0.005%.

[0005] In summary, completely removing the particles that pass through the filter during oil removal by adsorption, eliminating their impact on the product appearance quality, and improving product purity are of great significance for the extraction and application of high-purity nickel and cobalt metals. Summary of the invention

[0006] In order to solve the problem in the prior art that partially damaged particles are easy to filter through during oil removal by activated carbon adsorption, resulting in poor product appearance quality and low product purity, the present invention provides a method for deep purification of nickel-cobalt solution.

[0007] 1. A method for deep purification of nickel-cobalt solution, comprising the following steps:

[0008] (1) degreasing: degreasing the nickel-cobalt solution with activated carbon to obtain a degreasing solution; the nickel-cobalt solution is selected from one of nickel-cobalt sulfate, nickel-cobalt chloride and nickel-cobalt nitrate, and the nickel-cobalt solution contains oil;

[0009] (2) pH adjustment: adding inorganic acid or liquid alkali to the deoiled liquid to adjust the pH of the solution to 3.0-4.0 to obtain a pre-decarbonization liquid;

[0010] (3) Carbon removal: The pre-carbon removal liquid is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal liquid, and the power is turned on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution.

[0011] In the above step (1), the nickel-cobalt solution is specifically a nickel-cobalt raffinate and / or a nickel-cobalt stripping solution. The oil in the nickel-cobalt solution mainly comes from the residual extractant in the extraction process of the wet nickel refining process, and mainly exists in the form of dispersed oil. The present invention uses activated carbon for oil removal, which can basically remove the dispersed oil (particle size 10-100 μm). The activated carbon adsorption oil removal method is more commonly used. However, despite its good mechanical properties, it is still inevitable that the activated carbon particles will be damaged (for example, the pretreatment process, the transportation process, and the operation process will cause the activated carbon to be damaged). After the damage, the particle size of some carbon particles is very small. (can be less than 0.5μm), it is very easy to filter through during fine filtration, and finally when producing high-purity nickel salt and cobalt salt crystals, the filtered carbon particles are wrapped by the crystals during crystallization, causing the product to appear discolored and affecting the product appearance quality; when producing metallic nickel and metallic cobalt, the carbon particles are adsorbed on the cathode surface under the action of the electric field, which causes nickel or cobalt to be deposited on the cathode surface to form bulges, which cannot be eliminated by post-treatment measures, affecting the product appearance quality, especially after the electrolysis / electrodeposition system has been running for a long time, because part of the anode liquid needs to be returned as cathode liquid, the carbon particles have a particularly significant impact on the product appearance quality. In order to eliminate the impact on the appearance quality, it is necessary to deeply remove the activated carbon particles introduced during oil removal.

[0012] In step (2), in order to facilitate the removal of activated carbon particles by electrocoagulation, the pH of the deoiled liquid needs to be adjusted before electrocoagulation, and the pH is required to be 3.0-4.0. The pH for the formation of molybdate colloid is above 3.0. If the pH is lower than 3.0, the molybdenum dissolved from the anode during electrocoagulation cannot combine with oxygen and water to form molybdate colloid, and cannot adsorb and precipitate the activated carbon particles in the solution. If the pH is too high (for example, the pH is higher than 5.5), it is easy to cause the hydrolysis and precipitation of nickel and cobalt ions, reducing the recovery rate of nickel and cobalt. In order to take into account the recovery rate of nickel and cobalt and the removal rate of activated carbon particles and completely eliminate their influence on the appearance quality of the product, the pH of the solution needs to be adjusted to 3.0-4.0 before electrocoagulation.

[0013] In step (3), carbon is removed by electrocoagulation, wherein molybdenum metal is used as the anode, and the molybdenum metal is combined with water under the action of oxygen and electric field through electrolysis to generate molybdate colloid. The molybdate colloid has high activity and strong adsorption capacity for carbon particles suspended and dispersed in the solution. The carbon particles are destabilized under the action of electrocoagulation, and collide with the molybdate colloid to combine into a precipitate with a larger particle size. Therefore, the electrocoagulation method of the present invention can deeply remove carbon particles in the nickel-cobalt solution, and completely solve the problem that the damaged carbon particles are easy to penetrate during the activated carbon adsorption and degreasing, resulting in a decrease in the appearance quality of the product.

[0014] The reaction that occurs during electrocoagulation is:

[0015] Mo+4H2O electrolysis H2MoO4(s)+6H2(g)

[0016] Furthermore, in the nickel-cobalt solution, the oil concentration is 5-100 mg / L, and the nickel-cobalt ion concentration differs by 150-30,000 times.

[0017] When the concentration of nickel and cobalt ions differs by more than 150 times, the impurity content requirements of high-purity electrolytic metal nickel and cobalt, high-purity nickel salt and cobalt salt crystallization can be met. The solution finally obtained by the present invention is used for high-purity electrolytic nickel or electrolytic cobalt, high-purity nickel salt and cobalt salt crystallization, so the concentration of nickel and cobalt ions is required to differ by more than 150 times, preferably 150-30000 times.

[0018] Furthermore, the nickel-cobalt solution has a nickel concentration of 60-120 g / L and a cobalt concentration of 0.0002-0.1 g / L; or a cobalt concentration of 60-120 g / L and a nickel concentration of 0.0002-0.1 g / L.

[0019] If the concentration of nickel ions and cobalt ions in the nickel-cobalt solution is too low, a large amount of water will evaporate when used for evaporation and crystallization, which is not conducive to improving production efficiency. If the concentration of nickel and cobalt ions is too high, crystallization is likely to occur. Therefore, the preferred nickel concentration is 60-120 g / L and cobalt is 0.0002-0.1 g / L; or the cobalt concentration is 60-120 g / L and nickel is 0.0002-0.1 g / L.

[0020] Furthermore, in step (1), the activated carbon is deoiled by static deoiling or dynamic deoiling.

[0021] Both dynamic adsorption and static adsorption methods can be used for oil removal. The oil removal temperature is 20-55°C. For dynamic oil removal, the preferred flow rate of the raffinate and stripping liquid is 2-5BV / h. For static oil removal, the preferred amount of activated carbon is 5-20g / L, the oil removal time is 20-60min, and the iodine adsorption value of the activated carbon is required to be greater than 600mg / g.

[0022] Furthermore, in step (3), the pore size of the filter cloth during fine filtration is 1-10 μm.

[0023] After the electro-flocculation process is completed, a fine filtration process is required. During fine filtration, the pore size of the filter cloth is required to be less than 10 μm to increase the cleanliness of the solution and prevent the introduction of new particulate impurities. The pore size of the filter cloth is preferably 1-10 μm. If the pore size is too small, the filtration speed is slow, which is not conducive to improving production efficiency.

[0024] Furthermore, in step (3), during the electrocoagulation process, the cathode is selected from one of stainless steel, graphite, and iron, and the anode is metal molybdenum.

[0025] The selection of cathode and anode is crucial for the deep purification of nickel-cobalt solution. Suitable cathode and anode materials can improve electrolysis efficiency, reduce energy consumption, avoid the introduction of new impurities, and ensure that the purity and morphology of the product meet the requirements when the purified nickel-cobalt solution is used to produce nickel-cobalt products.

[0026] Furthermore, during the electrocoagulation process, an electric field is applied by a DC power supply to control the current density of the electrocoagulation to be 20-100 A / m 2 , the distance between the electrode plates is 0.5-2cm, the electrocoagulation time is 20-60min, the temperature is 20-60℃, and the cell voltage is 1.6-1.8V.

[0027] If the current density is too low or too high, the carbon removal effect is not good. If the current density is appropriately increased, the electrode reaction rate will increase, prompting the dissolution of anode Mo, and further generating molybdate colloid, which can be removed by adsorption and sedimentation. If the current density is too high, it may cause anode passivation, accelerate electrode passivation and increase the cell pressure, reduce the Mo dissolution rate, and further affect the generation rate of molybdate colloid, and ultimately weaken the carbon removal effect. If the current density is too low, the electrode reaction rate is slow, the processing efficiency is low, and the carbon removal effect is poor. The preferred current density is 20-100A / m 2 .

[0028] When the distance between the electrode plates is too large, the ion migration distance is too large, and the resistance encountered during migration is also large, which is easy to produce concentration polarization, thereby reducing the current efficiency, increasing the power consumption, and the carbon removal effect is not good. When the distance between the electrode plates is too small, the solute molecules that can move between the plates are small, the exchange amount is small, and the molybdate colloid is easy to accumulate between the plates, reducing the effective contact area between the colloid and the carbon particles, which is not conducive to sedimentation and the carbon removal effect is not good. If the distance between the electrode plates is too small, it is easy to cause a short circuit. Therefore, the preferred distance between the electrode plates is 0.5-2cm.

[0029] The present invention also includes step (4): electrolyzing the purified nickel-cobalt solution to obtain electrolytic nickel or electrolytic cobalt, or evaporating and crystallizing to obtain high-purity nickel salt or cobalt salt crystals.

[0030] The process of the present invention is as follows Figure 1 shown.

[0031] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0032] (1) The present invention adopts an electro-flocculation method to remove damaged carbon particles in a nickel-cobalt solution. Platinum metal is used as an anode. Through electrolysis, the platinum metal is combined with water under the action of oxygen and an electric field to form molybdate colloid. The molybdate colloid has high activity and strong adsorption capacity for carbon particles suspended and dispersed in the solution. The carbon particles are destabilized under the action of electro-flocculation, and collide with the molybdate colloid to form a precipitate with a larger particle size. Therefore, the electro-flocculation method of the present invention can deeply remove carbon particles in a nickel-cobalt solution;

[0033] (2) The electro-flocculation method of the present invention can remove carbon while also removing emulsified oil and dissolved oil in the solution. The particles of emulsified oil and the like undergo directional migration under the action of the electric field and undergo electrical neutralization on the anode surface, thereby destroying the stability of the emulsified oil, which is then adsorbed and precipitated by the generated molybdate colloid. Finally, the oil and the nickel-cobalt solution can be separated by fine filtration.

[0034] (3) The method of the present invention is simple, has low operating cost, high treatment efficiency, stable treatment effect, small equipment footprint, high degree of automation, and is easy to industrialize;

[0035] (4) The method of the present invention consumes only a small amount of anode, does not introduce new impurities, and has high solution cleanliness. The nickel-cobalt solution finally obtained is suitable for the production of high-purity nickel salts, cobalt salt crystals, metallic nickel, and metallic cobalt, which is of great significance for the extraction and application of high-purity nickel and cobalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0040] (1) Oil removal: The nickel-cobalt P507 raffinate containing an oil concentration of 5.00 mg / L, a nickel concentration of 60.92 g / L, a cobalt concentration of 0.0002 g / L, a pH of 3.63, and a main component of nickel sulfate was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was static deoiling (activated carbon was directly added to the nickel-cobalt P507 raffinate, and the reaction was stirred. The amount of activated carbon was 5 g / L, the deoiling temperature was 35°C, and the time was 20 min. The activated carbon used was coconut shell activated carbon, and its iodine adsorption was 610 mg / g. After the deoiling was completed, the solid and liquid were separated to obtain a deoiled liquid. The nickel and cobalt concentrations of the deoiled liquid remained unchanged, and the oil concentration was 1.10 mg / L.

[0041] (2) pH adjustment: The pH of the deoiled liquid is 3.85, which is within the range of 3.0-4.0. Therefore, there is no need to add acid or alkali to adjust the pH. At this time, the deoiled liquid is the pre-carbon removal liquid;

[0042] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and energized to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution; wherein the cathode is made of stainless steel, the anode is made of metal molybdenum, the anode and cathode plates are of the same size, and an electric field is applied by a DC power supply. The current density during electrocoagulation is specifically controlled to be 20A / m 2 , the distance between the electrode plates was 2.0 cm, the electrocoagulation time was 20 min, the temperature was 20°C, the cell voltage was 1.70 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 10 μm;

[0043] (4) The purified nickel-cobalt solution is electrolyzed to obtain electrolytic nickel. The electrolytic nickel conditions are: the same inter-electrode distance is 16 cm, the temperature is 50° C., and the current density is 200 A / m 2 During the electrolysis process, the cell voltage is 3.31V, and the surface of the high-purity electrolytic nickel obtained is flat and has no protrusions. The carbon content is 0.0002% (far lower than 0.005%), and the nickel purity reaches more than 99.99%; the purified nickel-cobalt solution is evaporated and crystallized to obtain nickel sulfate crystals. The outlet crystal slurry density during evaporation and crystallization is 1.64g / cm 3 , centrifuged, the obtained high-purity nickel sulfate crystals have no impurities, the carbon content is 0.0002%, and the purity reaches more than 99.99%.

[0044] Example 2

[0045] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0046] (1) Oil removal: The nickel-cobalt P507 stripping solution containing an oil concentration of 15 mg / L, a cobalt concentration of 60.10 g / L, a nickel concentration of 0.0002 g / L, a pH of 2.60, and a main component of cobalt sulfate was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was static deoiling (activated carbon was directly added to the nickel-cobalt P507 stripping solution, stirred for reaction, the amount of activated carbon was 10 g / L, the deoiling temperature was 20°C, the time was 30 min, and the activated carbon used was coconut shell activated carbon with an iodine adsorption of 809 mg / g). After the deoiling was completed, solid-liquid separation was performed to obtain a deoiled liquid, the nickel-cobalt concentration of the deoiled liquid remained unchanged, and the oil concentration was 2.04 mg / L;

[0047] (2) pH adjustment: The pH of the deoiled liquid was 2.88, which was not within the range of 3.0-4.0, so liquid caustic soda was added to adjust the pH to 3.00 to obtain the pre-decarbonization liquid;

[0048] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and powered on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution; wherein the cathode is graphite, the anode is metal molybdenum, the anode and cathode plates are of the same size, an electric field is applied by a DC power supply, and the current density during electrocoagulation is specifically controlled to be 50A / m 2 , the distance between the electrode plates was 1.5 cm, the electrocoagulation time was 30 min, the temperature was 35 °C, the cell voltage was 1.61 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 5 μm;

[0049] (4) The purified nickel-cobalt solution is electrolyzed to obtain electrolytic cobalt. The electrolytic cobalt conditions are: the same interelectrode distance is 15 cm, the temperature is 55° C., and the current density is 210 A / m 2 During the electrolysis process, the cell voltage is 3.36V, and the surface of the high-purity electrolytic cobalt obtained is flat and has no protrusions. The carbon content is 0.0003% (far lower than 0.005%), and the purity reaches more than 99.99%; the purified nickel-cobalt solution is evaporated and crystallized to obtain cobalt sulfate crystals. The outlet crystal slurry density during evaporation and crystallization is 1.54g / cm 3 , centrifuged, the high-purity cobalt sulfate obtained has no impurities, a carbon content of 0.0004%, and a purity of more than 99.99%.

[0050] Example 3

[0051] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0052] (1) Oil removal: The nickel-cobalt Cyanex272 raffinate containing an oil concentration of 52 mg / L, a nickel concentration of 92.92 g / L, a cobalt concentration of 0.062 g / L, a pH of 4.27, and a main component of nickel chloride was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was dynamic deoiling (deoiling temperature of 50° C., a Cyanex272 raffinate flow rate of 5 BV / h, and the activated carbon used was coconut shell activated carbon with an iodine adsorption of 800 mg / g). After the deoiling was completed, a deoiled liquid was obtained, in which the nickel-cobalt concentration of the deoiled liquid remained unchanged and the oil concentration was 1.50 mg / L.

[0053] (2) pH adjustment: The pH of the deoiled liquid was 4.15, which was not within the range of 3.0-4.0, so hydrochloric acid was added to adjust the pH to 4.00 to obtain the pre-decarbonization liquid;

[0054] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and powered on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution; wherein the cathode is iron, the anode is metal molybdenum, the anode and cathode plates are of the same size, and an electric field is applied by a DC power supply. The current density during electrocoagulation is specifically controlled to be 60A / m 2, the distance between the electrode plates was 1.0 cm, the electrocoagulation time was 40 min, the temperature was 40°C, the cell voltage was 1.71 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 2 μm;

[0055] (4) The purified nickel-cobalt solution is electrolyzed to obtain electrolytic nickel. The electrolytic nickel conditions are: the same inter-electrode distance is 16 cm, the temperature is 50° C., and the current density is 190 A / m 2 During the electrolysis process, the cell voltage is 3.48V, the surface of the electrolytic nickel obtained is flat and has no protrusions, the carbon content is 0.0005% (far lower than 0.005%), and the purity reaches more than 99.9%; the purified nickel-cobalt solution is evaporated and crystallized to obtain nickel chloride crystals, and the outlet crystal slurry density during evaporation and crystallization is 1.62g / cm 3 , centrifuged, the obtained nickel chloride crystals have no impurities, the carbon content is 0.0004%, and the purity reaches more than 99.9%.

[0056] Example 4

[0057] (1) Oil removal: The nickel-cobalt Cyanex272 stripping solution containing an oil concentration of 60 mg / L, a cobalt concentration of 85.5 g / L, a nickel concentration of 0.57 g / L, a pH of 2.98, and a main component of cobalt nitrate was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was dynamic deoiling (deoiling temperature was 45°C, the flow rate of the Cyanex272 stripping solution was 2 BV / h, and the activated carbon used was coconut shell activated carbon with an iodine adsorption of 800 mg / g). After the deoiling was completed, a deoiled liquid was obtained, in which the nickel-cobalt concentration of the deoiled liquid remained unchanged and the oil concentration was 1.16 mg / L.

[0058] (2) pH adjustment: The pH of the deoiled liquid is 3.25, which is within the range of 3.0-4.0. Therefore, there is no need to adjust the pH. The deoiled liquid is the pre-carbon removal liquid.

[0059] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and powered on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution, wherein the cathode is iron and the anode is metal molybdenum. The anode and cathode plates are of the same size. An electric field is applied by a DC power supply, and the current density during electrocoagulation is specifically controlled to be 100A / m 2 , the distance between the electrode plates was 0.5 cm, the electrocoagulation time was 60 min, the temperature was 40 °C, the cell voltage was 1.73 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 1 μm;

[0060] (4) The purified nickel-cobalt solution is evaporated and crystallized to obtain cobalt nitrate crystals. The outlet crystal density during evaporation and crystallization is 1.55 g / cm 3, centrifuged, the obtained cobalt nitrate crystals have no impurities, the carbon content is 0.0002%, and the purity reaches more than 98%.

[0061] Example 5

[0062] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0063] (1) Oil removal: The nickel-cobalt Cyanex272 stripping solution containing an oil concentration of 100 mg / L, a cobalt concentration of 120 g / L, a nickel concentration of 0.10 g / L, a pH of 2.32, and a main component of cobalt chloride was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was static deoiling (activated carbon was directly added to the Cyanex272 stripping solution, and the reaction was stirred. The amount of activated carbon was 20 g / L, the deoiling temperature was 55°C, and the time was 60 min. The activated carbon used was coconut shell activated carbon, and its iodine adsorption was 800 mg / g). After the deoiling was completed, a deoiled liquid was obtained. The nickel-cobalt concentration of the deoiled liquid remained unchanged, and the oil concentration was 3.26 mg / L.

[0064] (2) pH adjustment: The pH of the deoiled liquid was 2.40, which was not within the range of 3.0-4.0. Therefore, liquid caustic soda was added to adjust the pH to 3.18 to obtain the pre-decarbonization liquid;

[0065] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and powered on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution, wherein the cathode is iron and the anode is metal molybdenum. The anode and cathode plates are of the same size. An electric field is applied by a DC power supply, and the current density during electrocoagulation is specifically controlled to be 100A / m 2 , the distance between the electrode plates was 0.5 cm, the electrocoagulation time was 60 min, the temperature was 60 ° C, the cell voltage during the electrocoagulation process was 1.80 V, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 2 μm;

[0066] (4) The purified nickel-cobalt solution is electrolyzed to obtain electrolytic cobalt. The electrolytic cobalt conditions are: the same interelectrode distance is 15 cm, the temperature is 55° C., and the current density is 180 A / m 2 During the electrolysis process, the cell voltage is 3.25V, the surface of the electrolytic cobalt obtained is flat and has no protrusions, the carbon content in the electrolytic cobalt is 0.0003% (far lower than 0.005%), and the purity reaches more than 99.9%; the purified nickel-cobalt solution is evaporated and crystallized to obtain cobalt chloride crystals, and the outlet crystal slurry density during evaporation and crystallization is 1.50g / cm 3 , centrifuged, the obtained cobalt chloride crystals have no impurities, the carbon content is 0.0005%, and the purity reaches more than 99.9%.

[0067] Example 6

[0068] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0069] (1) Oil removal: The nickel-cobalt Cyanex272 raffinate containing an oil concentration of 100 mg / L, a nickel concentration of 120 g / L, a cobalt concentration of 0.10 g / L, a pH of 3.55, and a main component of cobalt sulfate was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was dynamic deoiling (deoiling temperature of 55°C, a Cyanex272 raffinate flow rate of 3 BV / h, and the activated carbon used was coconut shell activated carbon with an iodine adsorption of 800 mg / g). After the deoiling was completed, a deoiled liquid was obtained, in which the nickel-cobalt concentration of the deoiled liquid remained unchanged and the oil concentration was 1.28 mg / L.

[0070] (2) pH adjustment: The pH of the deoiled liquid is 3.60, which is within the range of 3.0-4.0. Therefore, there is no need to adjust the pH. The deoiled liquid is the pre-carbon removal liquid.

[0071] (3) Carbon removal: The pre-carbon removal solution is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal solution and powered on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution, wherein the cathode is stainless steel, the anode is metal molybdenum, the anode and cathode plates are of the same size, and an electric field is applied by a DC power supply. The current density during electrocoagulation is specifically controlled to be 100A / m 2 , the distance between the electrode plates was 0.5 cm, the electrocoagulation time was 60 min, the temperature was 60 ° C, the cell voltage was 1.77 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 2 μm;

[0072] (4) The purified nickel-cobalt solution is electrolyzed to obtain electrolytic nickel. The electrolytic nickel conditions are: the same interelectrode distance is 15 cm, the temperature is 55° C., and the current density is 220 A / m 2 During the electrolysis process, the cell voltage is 3.76V, the surface of the electrolytic nickel obtained is flat and has no protrusions, the carbon content is 0.0005% (far lower than 0.005%), and the purity reaches more than 99.9%; the purified nickel-cobalt solution is evaporated and crystallized to obtain nickel sulfate crystals, and the outlet crystal slurry density during evaporation and crystallization is 1.66g / cm 3 , centrifuged, the obtained nickel sulfate crystals have no impurities, the carbon content is 0.0004%, and the purity reaches more than 99.9%.

[0073] In order to illustrate the technical effect of the present invention, the inventors conducted the following comparative tests:

[0074] Comparative Example 1

[0075] The difference between Comparative Example 1 and Example 1 is:

[0076] In step (3) of comparative example 1, the anode is metal aluminum. The remaining steps are the same as those of example 1.

[0077] As a result, the obtained nickel sulfate crystals contained impurities, had a carbon content of 0.0013%, and a purity of only 91.86%.

[0078] Comparative Example 2

[0079] The difference between Comparative Example 2 and Example 1 is:

[0080] In step (3) of comparative example 2, the anode is metallic iron. The remaining steps are the same as those of example 1.

[0081] As a result, the obtained nickel sulfate crystals contained impurities, had a carbon content of 0.0056%, and a purity of only 96.24%.

[0082] Comparative Example 3

[0083] The difference between Comparative Example 3 and Example 2 is that:

[0084] In step (2) of comparative example 3, the pH is not adjusted to 3.00, that is, step (2) is omitted, and the specific steps are as follows:

[0085] A method for deep purification of nickel-cobalt solution comprises the following steps:

[0086] (1) Oil removal: The nickel-cobalt P507 stripping solution containing an oil concentration of 15 mg / L, a cobalt concentration of 60.10 g / L, a nickel concentration of 0.0002 g / L, a pH of 2.60, and a main component of cobalt sulfate was deoiled with activated carbon. The deoiling conditions were as follows: the deoiling method was static deoiling (activated carbon was directly added to the nickel-cobalt P507 stripping solution, and the reaction was stirred. The amount of activated carbon was 10 g / L, the deoiling temperature was 20°C, and the time was 30 min. The activated carbon used was coconut shell activated carbon, and its iodine adsorption was 809 mg / g). After the deoiling was completed, the solid and liquid were separated to obtain a deoiled liquid. The nickel-cobalt concentration of the deoiled liquid remained unchanged, and the oil concentration was 2.04 mg / L; the pH of the deoiled liquid was 2.88;

[0087] (2) Carbon removal: The deoiled liquid is transferred into an electrolytic cell, and the anode and cathode plates are respectively inserted into the deoiled liquid, and electricity is applied to perform electrocoagulation and carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution; wherein the cathode is graphite, the anode is metal molybdenum, the anode and cathode plates are of the same size, and an electric field is applied by a DC power supply. The current density during electrocoagulation is specifically controlled to be 50A / m 2 , the distance between the electrode plates was 1.5 cm, the electrocoagulation time was 30 min, the temperature was 35 °C, the cell voltage was 1.61 V during the electrocoagulation process, and the electrocoagulation liquid was finely filtered after the electrocoagulation was completed. The pore size of the filter cloth during the fine filtration was 5 μm;

[0088] (3) The purified nickel-cobalt solution was electrolyzed to obtain electrolytic cobalt. The electrolytic cobalt conditions were: the same interelectrode distance was 15 cm, the temperature was 55° C., and the current density was 210 A / m2 During the electrolysis process, the cell voltage was 3.36V. The surface of the high-purity electrolytic cobalt obtained was uneven, and there were a few protrusions on the electrolytic cobalt plate surface. The carbon content was 0.0068% (higher than 0.005%), and the purity reached more than 99.99%. The purified nickel-cobalt solution was evaporated and crystallized to obtain cobalt sulfate crystals. The outlet crystal slurry density during evaporation and crystallization was 1.54g / cm 3 , centrifuged, the cobalt sulfate obtained contained impurities, the carbon content was 0.0015%, and the purity reached 99.15%.

[0089] It can be seen from Comparative Examples 1 and 2 that when the electrocoagulation method is used to remove damaged carbon particles in the nickel-cobalt solution, the nickel sulfate crystal quality obtained by using molybdenum metal as the anode is the highest. It can be seen from Comparative Example 3 that the pH of the solution is also crucial in the electrocoagulation carbon removal process. If the pH is lower than 3.0, the carbon and impurity removal will not be thorough, resulting in an uneven surface of the electrolytic cobalt and the appearance of mixed colors in the cobalt sulfate.

[0090] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for deep purification of nickel-cobalt solution, characterized in that The steps include: (1) degreasing: degreasing the nickel-cobalt solution with activated carbon to obtain a degreasing solution; the nickel-cobalt solution is selected from one of nickel-cobalt sulfate, nickel-cobalt chloride and nickel-cobalt nitrate, and the nickel-cobalt solution contains oil; (2) pH adjustment: adding inorganic acid or liquid alkali to the deoiled liquid to adjust the pH of the solution to 3.0-4.0 to obtain a pre-decarbonization liquid; (3) Carbon removal: The pre-carbon removal liquid is transferred into the electrolytic cell, and the anode and cathode plates are respectively inserted into the pre-carbon removal liquid, and the power is turned on to perform electrocoagulation carbon removal. After carbon removal, fine filtration is performed to obtain a purified nickel-cobalt solution.

2. A method for deep purification of a nickel-cobalt solution as claimed in claim 1, characterized in that: In the nickel-cobalt solution, the oil concentration is 5-100 mg / L, and the nickel-cobalt ion concentration differs by 150-30,000 times.

3. A method for deep purification of a nickel-cobalt solution as claimed in claim 1, characterized in that: The nickel-cobalt solution has a nickel concentration of 60-120 g / L and a cobalt concentration of 0.0002-0.1 g / L; or a cobalt concentration of 60-120 g / L and a nickel concentration of 0.0002-0.1 g / L.

4. A method for deep purification of a nickel-cobalt solution as claimed in claim 1, characterized in that: In step (1), the activated carbon is deoiled by static deoiling or dynamic deoiling.

5. The method for deep purification of a nickel-cobalt solution according to claim 1, characterized in that: In step (3), the pore size of the filter cloth during fine filtration is 1-10 μm.

6. The method for deep purification of a nickel-cobalt solution according to claim 1, characterized in that: In step (3), during the electrocoagulation process, the cathode is selected from one of stainless steel, graphite, and iron, and the anode is metal molybdenum.

7. A method for deep purification of a nickel-cobalt solution as claimed in claim 6, characterized in that: During the electrocoagulation process, an electric field is applied by a DC power supply to control the current density of the electrocoagulation to 20-100A / m 2 , the distance between the electrode plates is 0.5-2cm, the electrocoagulation time is 20-60min, the temperature is 20-60℃, and the cell voltage is 1.6-1.8V.

8. The method for deep purification of a nickel-cobalt solution according to claim 1, characterized in that: The method also includes step (4): electrolyzing the purified nickel-cobalt solution to obtain electrolytic nickel or electrolytic cobalt, or evaporating and crystallizing the solution to obtain high-purity nickel salt or cobalt salt crystals.

Citation Information

Cited By

  • Method for reducing floating oil and blue dope in nickel-cobalt binary liquid

    CN121518819A